Faktor Yang Mempengaruhi Firm Financial Performance Perusahaan Manufaktur Yang Terdaftar Di BEI - Rinjani Sanusi Putri, Linda Santioso (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence on the influence of board independence, CEO duality, firm size, financial leverage, asset tangibility, and liquidity toward firm financial performance. The study drawson data from136 firms of manufacturing companies listed on the Indonesia Stock Exchange during 2015-2017. The results of this study indicate board independence, firm size, financial leverage, asset tangibility, and liquidity have a significant influence on firm financial performance, while CEO duality has no significant effect on firm financial performance. To further complement future research, make the sample count the right way, use a company that includes not only a manufacturing company, and uses a variable that has no been widely used that may influence firm’s financial performance.